Will a new NHS structure in England help recovery from the pandemic?. (3rd February 2021) - Alderwick, Hugh; Dunn, Phoebe; Gardner, Tim; Mays, Nicholas; Dixon, Jennifer
Abstract : The health policy challenges facing the NHS and government are enormous, but Hugh Alderwick and colleagues argue that a major reorganisation is not the solution